Juvenile resistance of barleys from the East Asian center of crop origin and domestication to powdery mildew - R. A. Abdullaev; I. N. Anisimova; O. N. Kovaleva; E. E. Radchenko (Труды по прикладной ботанике, генетике и селекции)
Background. A significant reduction in the yield of barley may be provoked by powdery mildew (causative agent: Blumeria graminis (DC.) Golovin ex Speer f. sp. hordei Marchal). A vast majority of cultivars approved for use in Russia are susceptible to the pathogen. Including genotypes protected by previously unused resistance genes into breeding practice is necessary to ensure the national food security. Barley landraces could become a fairly rich source of replenishment for the bank of effective pathogen resistance genes.Materials and methods. The study covered 950 barley accessions from the East Asian center of crop origin and domestication: 449 accessions from Japan, 313 from China, 173 from Mongolia, and 15 from Nepal. The experiments were carried out on young plants in a climatic chamber under artificial infection conditions. The northwestern (Pushkin, St. Petersburg) population of B. graminis served as an inoculum. Plant resistance was assessed using a scoring scale. The resistance of the selected forms was assessed twice.Results and conclusions. Significant variability of barley accessions from the countries of East Asia in their resistance to powdery mildew was observed. Symptoms of the disease were not found on plants of 16 studied forms. Weak or moderate development of the B. graminis mycelium was recorded for 21 accessions. Twenty-seven accessions were heterogeneous in the studied trait. Various levels of resistance were identified in 64 studied accessions (6.73%), among which 44 represented cultivars and breeding lines, and 20 were landraces. The percentage of accessions susceptible to the studied population of the pathogen was 93.27%.